Random-TD Function Approximator - Osman, Hassab Elgawi (Journal of advanced computational intelligence and intelligent informatics, 2009)
In this paper, adaptive controller architecture based on a combination of temporal-difference (TD) learning and an on-line variant of Random Forest (RF) classifier is proposed. We call this implementation Random-TD. The approach iteratively improves its control strategies by exploiting only relevant parts of action and is able to learn completely in on-line mode. Such capability of on-line adaptation would take us closer to the goal of more robust and adaptable control. To illustrate this and to demonstrate the applicability of the approach, it has been applied to a non-linear, non-stationary control task, Cart-Pole balancing and on high-dimensional control problems –Ailerons, Elevator, Kinematics, and Friedman–. The results demonstrate that our hybrid approach is adaptable and can significantly improves the performance of TD methods while speeding up the learning process.